The influence of individual oral hygiene of the mouth on the dental status of workers of metallurgical production - S. B. Ulitovsky; O. V. Kalinina; I. A. Butyugin; M. B. Kadyrov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
This review introduces readers to the modern problems of improving the dental care of the workers of metallurgical production in the new socio-economic conditions and basic methods of prevention of dental diseases. Presented data testify about the peculiarities of the dental status and the rules of individual oral cavity hygiene in the examined population.